(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
Optimizing the physiological status of lactating dairy cows is greatly influenced by feed quality, particularly the availability of adequate protein and minerals to support systemic functions. This study was conducted to evaluate the erythrocyte response of lactating Peranakan Friesian Holstein (PFH) dairy cows supplemented with lamtoro leaves (Leucaena leucocephala). Twelve lactating PFH dairy cows, aged 3–4 years, in the 4th to 8th month of lactation, and with an average body weight of 450 kg, were placed in a Randomized Block Design (RBD) consisting of two treatments and six blocks. The diet consisted of a 40:60 ratio of forage to concentrate, with the concentrate comprising rice bran, coconut meal, coffee husks, wheat flour, vitamins, minerals, and soybean meal. Lamtoro leaf supplementation was 10% for P0 and 20% for P1 based on the dry matter of the forage. Blood samples were collected via the jugular vein for analysis of hemoglobin (Hb), red blood cell count (RBC), hematocrit (Hct), and indices including Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC). Data were analyzed using ANOVA followed by Duncan’s test. The results showed that the addition of lamtoro had a significant effect (p<0.05) on MCV, MCH, and MCHC, while hemoglobin and red blood cell count showed a positive upward trend. MCV (p<0.01) increased significantly from 39.90 fL in P0 to 47.8 fL in P1. MCH also increased from 11.54 pg to 12.31 pg. MCHC increased from 29.94% to 33.73% (p<0.05), indicating better hemoglobin saturation. RDW remained stable at 33.62% and 33.81%, reflecting uniform erythropoiesis. The conclusion of this study is that lamtoro supplementation up to 20% improves several erythrocyte indices, indicating improved erythrocyte characteristics in lactating dairy cows.